Dental malpractice lawsuits in Costa Rica: analysis of 124 cases in the period 2015-2020 - Fernández Chaves, José Manuel (2021)
Introduction: In Costa Rica, dental malpractice lawsuits (professional liability) are classified under the crime of culpable injuries according to the Criminal Code of Costa Rica. The purpose of this study is to describe the characteristics of all the claims analyzed by the Forensic Dentistry Unit of the Department of Legal Medicine in a period of six years (2015-2020). Materials and methods: A detailed review was carried out in the database of the Legal Medicine System (SIMEL) of the Legal Medicine Department of the Organismo de Investigación Judicial (Judicial Investigation Agency) of all the complaints of dental "malpractice" filed since January 1, 2015 to December 31, 2020. The information collected was tabulated in Excel and classified by year, related dental discipline, sex of the complainant and the result of the expert analysis. Results: The data analysis determined a total of 124 complaints, the disciplines with the highest percentages were oral and maxillofacial surgery (39.52%), dental implants (16.94%) and orthodontics (12.9%). More than two thirds (66.12%) of the complaints correspond to women and within the results of the forensic report 10% of the cases were positive, 32% negative and 58% inconclusive. Conclusions: the complete dental record is essential to be able to determine a causal link between the investigated facts and the results of a treatment; in this study more than 50% of the files where incomplete, invasive procedures such as oral surgery generate a greater possibility of lawsuits that could be avoided through proper management of risks and complications, adequate patient-caregiver communication, and management of treatment expectations.